Nutritional Status in Northeast India: A Comprehensive Study Linking Protein-Energy Malnutrition with Regional Disease Burden - Pallathadka, Harikumar; Roy, Parag Deb (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Northeast India, with its distinct geographical, cultural, and socioeconomic landscape, may exhibit a unique nutritional profile influencing population health. Despite national efforts, the region faces health challenges potentially linked to specific nutritional deficiencies. To assess the nutritional status, specifically focusing on protein-energy malnutrition (PEM), in Northeast India and evaluate its association with the prevalence of non-communicable diseases (NCDs) including diabetes, hypertension, and kidney disease. A multi-stage, cross-sectional study was conducted across 32 districts in Northeast India (n=4,762) from June 2023 to February 2024. Data collection employed innovative community-based methods, including anthropometric measurements from tailoring establishments and health markers from local barber shops, complemented by comprehensive household surveys and clinical assessments. The study found significantly lower protein intake in Northeast India (47.3±8.2 g/day) compared to the national average (60.4±9.7 g/day, p<0.001). The prevalence of Protein-Energy Malnutrition (PEM) was 32.6% regionally, peaking at 41.3% in rural areas. Strong negative correlations were observed between protein intake and the prevalence of type 2 diabetes (r=-0.76, p<0.001), hypertension (r=-0.68, p<0.001), and chronic kidney disease (r=-0.72, p<0.001). Multivariate analysis confirmed PEM as an independent risk factor for these conditions after adjusting for confounding variables. This study provides compelling evidence of widespread protein-energy malnutrition in Northeast India and establishes a significant association with the increased burden of diabetes, hypertension, and kidney disease in the region. The findings highlight an urgent need for region-specific nutritional interventions focused on protein adequacy to address the growing epidemic of non-communicable diseases.